Multiscale Laboratory Study and Numerical Analysis of Water-Weakening Effect on Shale - Zhen Li; Shangge Liu; Wentao Ren; Jinjin Fang; Qinghua Zhu; Zhilin Dun (Advances in Materials Science and Engineering)
Water-weakening effect is one of the most important factors inducing large deformation and stability problems of shale strata in the Huangjiazhai Tunnel. The influence of water on shale with various water contents and its mechanism still needs more study. In this paper, the X-ray diffraction and water absorption test were first conducted to determine the influence of mineral components on water-rock interaction. Then, a series of rock mechanical tests, including uniaxial compressive test, Brazilian disk test, and triaxial compressive test, were carried out on shale under dried condition, wetted condition with various water contents, and saturated condition. For the uniaxial compression, tension, and triaxial compression, the softening coefficient could reach 0.38, 0.63, and 0.52, respectively. Based on the macroscale experiments, a numerical case study of tunnel excavation was investigated to evaluate the water effect. Finally, with the aid of scanning electron microscope and failure morphology, the mechanism of water-weakening effect on shale was discussed from microscopic and macroscopic perspectives. The thickness of the double layer increases with the increase of water immersion time. This paper provides a set of useful data for reference in construction in shale strata, and a methodology to evaluate water-weakening effect through laboratory and numerical modelling approaches.